Profitability of Islamic Banks in the Pressure of Productive, Consumptive, and CKPNAK Problematic Financing - Achmad Fauzi; Etty Murwaningsari; Tatik Marjanti (Universitas Mercu Buana, 2026)
Objectives: The profitability of Islamic banks does not always decrease directly when non-performing financing increases. The impact is different between productive and consumptive financing, and is influenced by the dynamics of CKPNAK costs. Therefore, this assessment is important because previous research used a lot of aggregate NPFs, so it has not sufficiently explained the risk path based on financing segments. The purpose of this study is to analyze the influence of Problematic Productive Financing and Problematic Consumptive Financing on the profitability of Islamic banks in Indonesia, either directly or through Current Productive Financing, Current Consumptive Financing, and CKPNAK Costs.Methodology: The study uses a quantitative approach with monthly data on the Indonesian Islamic banking industry for the period January 2010–July 2023 and analyzed using PLS-SEM.Finding: PPB does not have a direct effect on profitability, but increases CKPNAK Costs. PKB reduces PKL and profitability directly. PKL increase profitability, while PPL does not always strengthen profitability. The novelty of this research is that this study separates the risks of productive and consumptive problematic financing and places CKPNAK as a risk transmission mechanism.Conclusion: The profitability of Islamic banks is more accurately understood through risk management based on the financing segment.